Análise do sistema de produção e da sustentabilidade de propriedades familiares orgânicas no município de Rio Claro (SP) - Silva, Rafaela Aparecida da (Universidade Federal de São Carlos, 2012)
The purpose of this dissertation is to analyze the production systems and the economical, socio-political and environmental sustainability level of organic family farms in the municipality of Rio Claro, SP, Brazil. It is assumed that organic farming is considered environmentally sustainable insofar as, among other factors, organic fertilizers and not synthetic pesticides are used. It is considered economically sustainable when it is able to reproduce itself; and socio-politically sustainable when it seeks to change the attitudes and values of the people involved. Besides secondary data gathered about the municipality, the identification of the farmers was carried out through researches done at public institutions related to the rural area, contacts made with other researchers, meetings of the municipality Family Farmers Association and conversations with the farmers. A prior conversation was held with the farmers in order to identify the characteristics related to their profiles, which are better detailed with the semi-structured interview. The research involved seven farmers and, based on the interviews, 18 economical, 20 socio-political and 34 environmental sustainability indicators were established. The main aspects observed were the strict relationship with the X Company and the positive and negative impacts it caused, in addition to the heterogeneity existing among the family about different aspects; however, there are similarities between the problems they face, such as the distance from the public institutions, as well as shortage of labor force. Growing vegetables is the principal commercial activity of these families. As for the indicators, the farmers showed a great interest both in the economical aspects and in the approach to soil fertility and management. These elaborate indicators interact among themselves, making it possible to systematically evaluate and analyze the data. In general terms, the families do not show sustainable properties. Nevertheless, families A and C showed better results related to this ideal, in comparison with the others.
Assessment of the production system and sustainability of organic family farms in the municipality of Rio Claro, SP, Brazil
Keywords: Agricultura familiar; Indicadores de desenvolvimento sustentável; Sistemas de produção; Rio Claro (SP); CIENCIAS AGRARIAS